2023
DOI: 10.14202/vetworld.2023.322-328
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter spp. in broilers in North Lebanon

Abstract: Background and Aim: Great attention has been given recently to the prevalence of different Campylobacter spp. in poultry since the latter are considered the major contributing reservoir of human campylobacteriosis. In Lebanon, the occurrence of campylobacteriosis in humans is high. The aim of our first-of-its-kind study in the country was to estimate the prevalence of Campylobacter spp. in broilers from a convenient sample of farms in North Lebanon. Materials and Methods: One hundred twenty-five fecal samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This observation could be due to cross-contamination by E. coli from resistant carrier chickens slaughtered on the same day or contamination by resident flora with AMR in the slaughterhouse [47]. These data are consistent with previously published studies indicating that antimicrobial resistance in broilers not exposed to ENR showed changes over time [44,57].…”
Section: Discussionsupporting
confidence: 91%
“…This observation could be due to cross-contamination by E. coli from resistant carrier chickens slaughtered on the same day or contamination by resident flora with AMR in the slaughterhouse [47]. These data are consistent with previously published studies indicating that antimicrobial resistance in broilers not exposed to ENR showed changes over time [44,57].…”
Section: Discussionsupporting
confidence: 91%
“…C. fetus colonizes the intestines of cattle and sheep which act as the reservoir of the microorganism [48,49]. It is a well-known pathogen in these species causing abortion and infertility [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The overall C. jejuni prevalence among the different groups was very strongly positively correlated to the large size of the flock (more than 30 birds) and to the presence of small ruminants (R = 0.832, p < 0.001). C. jejuni is known to colonize the digestive tract of warm-blooded hosts [48] infecting thus the poultry. Depending on the method, 96 to 98 strains were isolated making C. jejuni the most prevalent of all Campylobacter species (Table 2), a finding agreeing with similar findings of other authors who reported that this species is the most dominant and poultry is considered as its primary reservoir [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed the prevalence of Campylobacter spp. in broilers from North Lebanon, with high infection rates in both open rearing system (92%) and closed rearing system (85%) [ 6 ]. Campylobacter may infect broilers and chicken carcasses at any stage of the broiler supply chain.…”
Section: Introductionmentioning
confidence: 99%